1999
DOI: 10.1126/science.283.5402.686
|View full text |Cite
|
Sign up to set email alerts
|

Acetogenesis from H 2 Plus CO 2 by Spirochetes from Termite Guts

Abstract: Pure cultures of termite gut spirochetes were obtained and were shown to catalyze the synthesis of acetate from H2 plus CO2. The 16S ribosomal DNA sequences of two strains were 98 percent similar and were affiliated with those of the genus Treponema. However, neither was closely related to any known treponeme. These findings imply an important role for spirochetes in termite nutrition, help to reconcile the dominance of acetogenesis over methanogenesis as an H2 sink in termite hindguts, suggest that the motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
245
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(247 citation statements)
references
References 27 publications
2
245
0
Order By: Relevance
“…These two species reside in close proximity in the hindgut of the dampwood termite Zootermopsis angusticolis , wherein (as in most termites) a diversity of spirochetes constitute a large portion of the total gut microbiota (Breznak, 2002). Previous studies suggest that these bacteria have separate physiological roles in the complex mutualism (Leadbetter et al, 1999;Lilburn et al, 2001;. However, to what extent they interact with and impact each other and other gut species is less well examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These two species reside in close proximity in the hindgut of the dampwood termite Zootermopsis angusticolis , wherein (as in most termites) a diversity of spirochetes constitute a large portion of the total gut microbiota (Breznak, 2002). Previous studies suggest that these bacteria have separate physiological roles in the complex mutualism (Leadbetter et al, 1999;Lilburn et al, 2001;. However, to what extent they interact with and impact each other and other gut species is less well examined.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these tasks, as implicated by expression and activity data from this and previous studies, are presented in Figure 4. They include acetate production during sugar fermentation and CO 2 -reductive acetogenesis, H 2 cycling, nitrogen fixation, amino-acid biosynthesis and vitamin and co-factor production (Leadbetter et al, 1999;Lilburn et al, 2001;. In return, the termite provides its microbiota with finely ground particles of recalcitrat carbon and energy source, lignocellulose and a controlled environment.…”
Section: Od 600nmmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of other Dhc-containing dechlorinating microbial communities have also detected Spirochetes (Gu et al, 2004;Macbeth et al, 2004;Duhamel and Edwards, 2006). Based on what is known of Spirochetes in general, they may be fermenters or homoacetogens in these communities (Leadbetter et al, 1999;Madigan et al, 2008). Clone libraries are known to be susceptible to PCR and cloning biases (von Wintzingerode et al, 1997), and some studies have found Spirochetes in particular to be underrepresented in some clone libraries (Campbell and Cary, 2001;Hongoh et al, 2003).…”
Section: Methanobacteriummentioning
confidence: 99%
“…Because hydrogenases can catalyze both the formation and degradation of molecular hydrogen, the presence of hydrogenase genes does not differentiate the organisms that are producing hydrogen from those that are consuming it. Based on knowledge of other organisms in these taxonomic groups, however, the Clostridiaceae, the Desulfovibrio and the Spirochete are potential fermenters that produce hydrogen, although some may also be homoacetogens, consuming hydrogen and carbon dioxide to produce acetate (Leadbetter et al, 1999;Madigan et al, 2008). The methanogens likely consume hydrogen as an electron donor, competing with Dhc (Madigan et al, 2008).…”
Section: Methanobacteriummentioning
confidence: 99%